2022
DOI: 10.3389/fendo.2022.1023635
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thyroid function on assisted reproduction outcomes in euthyroid infertile women: A single center retrospective data analysis and a systematic review and meta-analysis

Abstract: BackgroundThe influence of thyroid-stimulating hormone (TSH) on gestational outcomes have been studied and checked whether differing TSH levels are relevant on human reproduction outcomes. International guidelines recommend TSH values <2.5 mIU/L in women trying to conceive, since values above this level are related to a higher frequency of adverse reproductive outcomes. This study aimed to evaluate whether TSH values correlate with different gestational outcomes in euthyroid infertile women without auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Hypo- and hyperthyroidism have adverse effects on female reproduction and are associated with a wide range of reproductive disorders, including abnormal sexual development, disturbances in menstruation and ovulation, and infertility ( 108 ). Furthermore, AIT presence in euthyroid women was associated with unexplained infertility, miscarriage, recurrent miscarriage, low fertilization rates, poor embryo quality in assisted reproductive technologies (ARTs), preterm delivery, and maternal post-partum thyroiditis ( 109 111 ). Anti-thyroid antibodies were detected in the ovarian follicular fluid of women with hypothyroidism at levels correlating with serum antibody levels, and their presence was associated with lower fertilization rates ( 96 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypo- and hyperthyroidism have adverse effects on female reproduction and are associated with a wide range of reproductive disorders, including abnormal sexual development, disturbances in menstruation and ovulation, and infertility ( 108 ). Furthermore, AIT presence in euthyroid women was associated with unexplained infertility, miscarriage, recurrent miscarriage, low fertilization rates, poor embryo quality in assisted reproductive technologies (ARTs), preterm delivery, and maternal post-partum thyroiditis ( 109 111 ). Anti-thyroid antibodies were detected in the ovarian follicular fluid of women with hypothyroidism at levels correlating with serum antibody levels, and their presence was associated with lower fertilization rates ( 96 ).…”
Section: Resultsmentioning
confidence: 99%
“…Anti-thyroid antibodies were detected in the ovarian follicular fluid of women with hypothyroidism at levels correlating with serum antibody levels, and their presence was associated with lower fertilization rates ( 96 ). PCOS was included among autoimmune-mediated disorders, such as endometriosis and premature ovarian failure ( 111 113 ). AIT presence was associated with unexplained infertility and implantation failure, irrespective of PCOS ( 114 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to the European Thyroid Association’s most recent recommendation for thyroid hormone suppression in TAI-positive patients is that TSH levels should remain below 2.5 µIU/mL, before IVF treatment is initiated. In contrast, variation in TSH levels within the normal range is not associated with pregnancy and delivery rates in women without autoimmune thyroid disease who underwent IVF treatment [22]. Thyroid hormone treatment of TAI-negative euthyreoid infertile women is not recommended before IVF treatment [13].…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, a more recent study of women without infertility found a negative association between TPOAbs levels and natural conception rates [ 158 ]. Investigating the impact of TSH levels versus those of autoimmunity, d’Assunção et al identified no differences in pregnancy rates among infertile women with AITD undergoing IVF when comparing ‘low’ vs. ‘high’ TSH (<2.5 vs. >2.5 mU/L) [ 159 ], suggesting that autoimmune destruction rather than reduced serum TSH links thyroid and reproductive pathologies.…”
Section: Thyroid Hormones and Reproductive Physiologymentioning
confidence: 99%